Overview of Patient Knowledge About The Use of Honey for Decubitus Wound Healing - Silalahi, Bernita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Definition of a decubitus wound is a localized area with necrotic tissue which usually occurs on the protruding bone surface, as a result of long-term pressure which causes an increase in capillary pressure. Decubitus at Imelda General Hospital for Indonesian workers in Medan 2020. Collecting Data In this study using observation. The study population was all patients regarding the benefits of honey for the treatment of pressure sores, time and place at the Imelda General Hospital for Indonesian workers in Medan in July 2020. The sample taken with a total sampling technique was 30 people. Based on the results of the study, the majority of the performance of patient knowledge about the benefits of honey for the treatment of pressure sores with a good category of 21 respondents (70%) and a minority of enough categories 4 respondents (30%).